Effect of Prolonged-Release Pirfenidone on Renal Function in Septic Acute Kidney Injury Patients (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Acute kidney damage is severe medical consequence that has a poor prognosis on its own. AKI occurs in around one out of every five patients with non-severe sepsis, rising to two out of three in critically sick patients Aim in research we aimed to assess impact of PR-PFD on renal function in studied cases with sAKI. Studied cases and techniques This research was randomized, double-blind, parallel-design clinical trial showed in single university hospital. Results there was variation among studied groups as regard pH, serum Na & platelets at day1 & statistical variation among studied groups as regard pH, serum K and platelets at day1. In group A there was variation among day 1 and day 7 as regard creatinine, serum HCO3, serum K, serum Na, Hb, serum uric acid, leukocytes and platelets. In group B there was variation among day 1 and day 7 as regard creatinine, pH, serum K, Hb, leukocytes and platelets. In group C there was variation among day 1 and day 7 as regard creatinine, serum K, serum Na, serum uric acid, leukocytes and platelets. Conclusion: In conclusion, PR-PFD was safe in terms of adverse events and improves kidney function when compared to placebo in patients with septic AKI. For our findings to be verified, more research is required.